IMAGINATION MODEL FOR LEARNING WRITING POETRY - Dewi Ariani (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
The aims of this study are (1) to develop the initial product design, (2) describe the results of expert validation and practitioner as well as field try-out,  (3) develop a product based on feed- back and suggestions from the experts,  and (4) describe the revised imaginations  model profile. This study uses a research-and-development model  proposed by Borg and Gall. The data were collected through interview guide and questionnaire. The results showed that the imagination model that is developed in the form of teacher guide book is suitable to be implemented for poetry writing teaching and learning process.